Determinants of overall survival in lung cancer in Kazakhstan: a retrospective cohort study using classical survival analysis - Avizova, Zeinep; Myssayev, Ayan; Iztleuov, Yerbolat; Mussin, Nadiar; Tamadon, Amin (Acta Biomedica Atenei Parmensis, 2026)
Background: Lung cancer is the leading cause of cancer-related death worldwide, but population-based survival data from Central Asia are scarce. Kazakhstan has a substantial lung cancer burden, yet little is known about survival and its determinants. This study aimed to identify demographic and clinical predictors of overall survival (OS) among lung cancer patients in Kazakhstan. Research design and Methods: We conducted a retrospective cohort study using the National Cancer Registry of Kazakhstan. Adults (≥18 years) with primary lung cancer diagnosed between 1 January 2019 and 31 December 2023 were analyzed. OS was defined as days from diagnosis to death or last follow-up. Kaplan–Meier methods estimated OS and compared survival by demographic, socioeconomic, and tumor characteristics. Cox proportional hazards models identified independent prognostic factors. Results: 13,402 patients were included (mean age 64.1 years; 79.4% male; 62.2% urban). Squamous cell carcinoma (34.9%) and stage III disease (47.5%) predominated. Median OS was 167 days (IQR 53–399), and 75.9% of patients died during follow-up. In multivariable analyses, older age, male sex, lower social status, unfavorable diagnostic circumstances, non-adenocarcinoma histology, and advanced stage were associated with higher mortality, while urban residence was protective. Tumor stage was the strongest predictor of OS. Conclusions: Lung cancer survival in Kazakhstan is poor, with patients presenting at advanced stages. Demographic and socioeconomic characteristics are independent determinants of OS. These findings support efforts to improve early detection, broaden access to lung cancer care—especially for rural and disadvantaged populations—and incorporate risk stratification into cancer control policies.